Pengaruh Durasi Penggunaan Game Online Roblox terhadap Moralitas Pelajar SD Berbasis Islamic Behavioral Contract - Ayesha Nihel Fazila; Ummy Chairiyah (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2025)
This study aims to examine the effect of the Islamic Behavioral Contract intervention on improving the morality of elementary school students who are affected by high durations of playing the online game Roblox. This quantitative research employed a One Group Pretest–Posttest design with the Purposive Sampling technique, involving five (N=5) students from SD Islam Terpadu Cendekia Lamongan whose initial morality scores (Pretest) were categorized as High (Low Morality). Data were analyzed using the Wilcoxon Signed Ranks Test.The results showed that the average morality score decreased significantly from 43.40 (Low Morality) in the Pretest to 26.20 (High Morality) in the Posttest. The hypothesis test yielded an Asymp. Sig. (2-tailed) value of 0.043 (p < 0.05). These findings indicate that the Islamic Behavioral Contract intervention has a significant effect on improving students’ morality. This approach is effective because it integrates structured behavior modification with Islamic values, successfully restoring students’ self-control, sense of responsibility, and ethical awareness.